Steam distilled extract of ginger is a potent mediator of apoptosis in endometrial cancer cells via the modulation of the p53 and BcI-2 pathways - Ludwig, Kai (My University, 2012)
Development for new therapeutic and preventative agents in the treatment of gynecological cancers is in constant need. In the cunent study, we demonstrate that the steam distilled extracts of ginger are potent mediators of apoptosis in endometrial cancer cells. The treatment of endometrial cancer cells with the steam distilled extract of ginger results in significant decrease in the mitochondrial membrane potential, increase in the expression of cleaved caspase-3, phosphorylation ofP53, and a significant decrease in the expression of Bcl-2. These results exhibit the potential of ginger extract to be used in the treatment and/or prevention of endometrial cancer.
20 p.
Keywords: Gynecology; Obstetrics; Biology; Biochemistry